An atypical new aquatic species of Habenaria (Orchidaceae, Orchidoideae) from Goiás, Brazil - Santos, Igor Soares Dos; Silva, Marcos José Da (Phytotaxa, 2025)
Habenaria brachycalcarata, a new aquatic species from the state of Goiás, Brazil, is described, illustrated, mapped and commented in relation to its distribution, flowering and fruiting season, conservation status, morphological relationships and systematic position.